The Effect of Using Easy Stories In English Podcast on Spotify Application on Students Listening Comprehension - N, Nuriana; Daulay, Ernita; Salmiah, Maryati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The research aims to determine whether using Easy Stories in English Podcasts on the Spotify application is effective for improving students' listening comprehension. The study involved two classes from XI SMA Negeri 1 Permata: 25 students in class XI.3 served as the experimental group, while 25 students in class XI.2 were the control group. The results indicate that using Easy Stories in English Podcasts on Spotify significantly improved test scores, particularly in listening skills. This improvement is reflected in the scores of the students. The test data were analyzed using normality and homogeneity tests, followed by a t-test. The average score for listening skills among students using the Easy Stories in English Podcasts was 69.60, compared to 55.60 for those not using the podcasts. This result leads to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). Therefore, it can be concluded that utilizing Easy Stories in English Podcasts on Spotify enhances students' listening skills.